Potential Antibacterial Activity of Bioactive β-sitosterol from Root Bark of Rhizophora apiculata from Lampung Coastal - Rahmat Kurniawan; Tati Suhartati; Yandri AS; Desi Meriyanti; Sukrasno Sukrasno (Jurnal Kimia Sains dan Aplikasi, 2021)
β-sitosterol is an essential bioactive phytosterol naturally present in plant cell membranes. It has a coincident structure with animal cholesterol. This investigation reported isolation, structure analysis, and an antimicrobial assay of β-sitosterol from the root bark of Bakau Minyak (Rhizophora apiculata) from Lampung coastal. The isolation of β-sitosterol was carried out through maceration using methanol, separation by vacuum liquid chromatography (VLC), and purification by column chromatography (CC) using ethyl acetate/n-hexane (2:8) as eluent. The structure of β-sitosterol was determined using spectroscopic analysis (UV-Vis, FT-IR, 13C-NMR, 1H-NMR, DEPT, and GC-MS). The pure β-sitosterol has 107.4 mg of white needle crystalline compound, the compound melting point about 140.7-141.2oC, the molecular mass confirmed by m/z 414, and UV absorption detected at λ 203.9 nm. The β-sitosterol antimicrobial bioactivity assay has shown potential activity to be developed as a lead compound against E. coli.